Optoelectronic mixing with high-frequency graphene transistors - A. Montanaro (Nature Portfolio, 2021)
Here, the authors report optoelectronic mixing up to 67 GHz using high-frequency back-gated graphene field effect transistors (GFETs). These devices mix an electrical signal injected into the GFET gate and a modulated optical signal onto a single layer graphene channel.